2013
DOI: 10.1111/jphp.12148
|View full text |Cite
|
Sign up to set email alerts
|

Vildagliptin: an anti-diabetes agent ameliorates cognitive deficits and pathology observed in streptozotocin-induced Alzheimer's disease

Abstract: These robust therapeutic effects of vildagliptin demonstrate a unique mechanism for Aβ and tau clearance and reverse the cognitive deficits and pathology observed in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 51 publications
(91 reference statements)
4
78
0
Order By: Relevance
“…Peripherally‐administered exenatide and liraglutide prevented or improved memory performance in various rodent models of AD72, 73, 74, including in one late stage AD model75, and one diabetes‐related AD model76. Peripherally‐administered DPP‐4 inhibitors sitagliptin, vildagliptin and saxagliptin improved memory impairment in AD rodents77, 78, 79. In addition to these cognitive effects, incretins have beneficial effects on synaptic plasticity in rodent models of AD.…”
Section: Type 2 Diabetes Mellitus Dementia and Incretin‐based Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripherally‐administered exenatide and liraglutide prevented or improved memory performance in various rodent models of AD72, 73, 74, including in one late stage AD model75, and one diabetes‐related AD model76. Peripherally‐administered DPP‐4 inhibitors sitagliptin, vildagliptin and saxagliptin improved memory impairment in AD rodents77, 78, 79. In addition to these cognitive effects, incretins have beneficial effects on synaptic plasticity in rodent models of AD.…”
Section: Type 2 Diabetes Mellitus Dementia and Incretin‐based Therapiesmentioning
confidence: 99%
“…Peripherally‐administered liraglutide reduced both Aβ and APP levels72, even in a late‐stage AD rodent model75. Furthermore, peripherally‐administered sitagliptin, saxagliptin and vildagliptin lowered the levels of Aβ77, 78, 79. With regard to tau metabolism, studies in AD rodents showed that centrally‐administered (Val 8 )GLP‐168 and geniposide71, as well as peripherally‐administered exendin‐4 and liraglutide74, 76, reduced tau phosphorylation68, 71.…”
Section: Type 2 Diabetes Mellitus Dementia and Incretin‐based Therapiesmentioning
confidence: 99%
“…As with GLP-1 analogues, DPP4 inhibitors have also shown promise in treatment of other conditions. Linagliptin has been shown to protect against stroke in animal models and both vildagliptin and saxagliptin attenuates the effects of steptozotocin induced-AD in rats [71][72][73].…”
Section: The Role Of Gip Glp-1 and Dpp4mentioning
confidence: 99%
“…Vildagliptin, a DPP-4 inhibitor which increases circulating GLP-1 levels, has been shown to ameliorate the deposition of amyloid beta and tau phosphorylation in a streptozotosin induced animal model of diabetes [93] . A study by Omar et al [94] using a high fat diet induced obesity model in mice of advanced age has demonstrated that Vildagliptin confirms other rodent models of diabetes in preserving beta cell mass mainly through inducing beta cell proliferation and reducing beta cell apoptosis [94][95][96] .…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
“…Hypoglycaemia was significantly less in the patients taking DPP-4 inhibitors. These patients had significantly less transitory cerebral ischaemic attacks whereas other cardiovascular events were of borderline significance.There are 6 DPP-4 inhibitors (e.g., Sitigliptin, Linagliptin, Vildagliptin, Alogliptin, Saxagliptin, Teneligliptin) on the market minor variation in their chemical composition have not been translated to particular benefit although it should be noted that linagliptin is mostly excreted in pathways other than the kidney and hence dosage does not have to be reduced in moderate renal failure.Vildagliptin, a DPP-4 inhibitor which increases circulating GLP-1 levels, has been shown to ameliorate the deposition of amyloid beta and tau phosphorylation in a streptozotosin induced animal model of diabetes [93] . A study by Omar et al [94] using a high fat diet induced obesity model in mice of advanced age has demonstrated that Vildagliptin confirms other rodent models of diabetes in preserving beta cell mass mainly through inducing beta cell proliferation and reducing beta cell apoptosis [94][95][96] .…”
mentioning
confidence: 99%